Revealing the Relationship Between Macrostructures and Inclusions Across the Thickness Direction of Q235B Slabs - Bo Wang; Jinwen Jin; Chao Gu; Ze Wei; Ziyu Lyu; Lidong Xing; Yanping Bao (Crystals)
Macrostructures and inclusions are both vital for slabs because the quality of slabs is largely affected by them. However, the relationship between macrostructures and inclusions in the thickness direction of the slab is still unclear. Hence, in this paper, the relationship between macrostructures and inclusions was revealed by laboratory experiments and theoretical calculations. The laboratory experiments included carbon and sulfur content testing, direct reading spectroscopy, scanning electron microscopy, and automatic inclusion scanning. The experimental results showed that the distribution of macrostructures was symmetrical from the inner and outer arc to the center. From the edge to the center of the slab, the variation in macrostructures was columnar crystal zone (CZ)→columnar-to-equiaxed transition (CET)→equiaxed crystal zone (EZ). Furthermore, the content of sulfur and manganese first decreased and then increased from the inner arc to the outer arc. The number density and area fraction of MnS inclusions in different macrostructures were CZ > CET > EZ. The average size of MnS in different macrostructures was CZ > EZ > CET. Moreover, the morphology of MnS inclusions was ellipse and rod in CZ, irregular dendrite in CET, and multilateral in EZ. Additionally, theoretical calculation results showed the maximum precipitation and initial precipitation temperature of MnS inclusions in different macrostructures were CZ > EZ > CET. Meanwhile, the theoretical precipitation radius of MnS inclusions in different macrostructures was CZ > EZ > CET.